FISH TAPHONOMY AND TRIASSIC ANOXIC BASINS FROM THE ALPS: A CASE HISTORY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
Anoxic basins, rich in fossil vertebrates, are frequently represented in the Middle and Upper Triassic rocks of both Southern and Northern Calcareous Alps. Some of the localities have been known since the second half of the XIX century and have yielded a great deal of specimens (Formazione di Besano, Seefelder Schichten), some others have been only recendy found (Calcare di Zorzino). In the past times, these sites have generally been the object of economical rather than paleontological interests: their bituminous levels, in fact, were mainly exploited for pharmaceutical purposes. Their present economical interest resides in that they may have been oil source-rocks. The formations in question have a medium/high total organic matter content (TOC, up to 40%). This, together with the presence of abundant, well preserved fossil vertebrates, have always led the previous Authors to think the basins bottom was anoxic; they assumed, in fact, that marine vertebrates fossilizate mainly under anoxia. Nonetheless, the taphonomic study of these vertebrate remains, here carried on for the first time, only in some cases supports this idea; in the others, most of all as concerns the Formazione di Besano, it has allowed the proposition of a different model. Fossils, in fact, often lie isooriented and disarticulate, with unimodal dispersal of the single elements. This implies the presence of light bioturbation and currents at the bottom and thus a disaerobic, rather than anoxic environment. Regarding other units, such as the Calcare di Zorzino and the Kalkschieferzone, the anoxic bottom conditions are well supported by the preservation of very small sized, completely articulated specimens, though the TOC shows remarkably lower rates than in the Formazione di Besano.
Keywords: Anoxic environment; Taphonomy; Vertebrates; Alps; Triassic